Memorial para promoção para o Nível E – Professor Titular da Carreira do Magistério Superior - Gasnier, Thierry Ray Jehlen (Brasil, 2019)
In this memorial were described the aspects considered significant by the author about his professional career, contributions as a teacher, researcher and manager, a discussion of the results obtained and the consequences and consequences of his performance.